Large-Scale Survey of Missing Deciduous Anterior Teeth on Medical Examination at the Age of 3.5 Years - Tsutomu Otsuchi; Yuko Ogaya; Yuto Suehiro; Rena Okawa; Kazuhiko Nakano (MDPI AG, 2022)
Tooth anomalies in childhood may negatively affect the healthy development of the dentition and occlusion; hence, it is important to examine the actual oral condition at an early stage. The present study was performed to understand the state of missing deciduous anterior teeth in children aged 3.5 years who underwent dental checkups in Matsubara City. In total, 3508 children received oral examinations, and items such as erupted deciduous teeth and teeth anomalies were recorded. Among these children, those with missing anterior deciduous teeth were selected, and their details were analyzed. In the 216 children, there were 266 missing anterior deciduous teeth. Congenitally missing anterior deciduous teeth were observed in 80 children, and fused teeth were observed in 128 children. The missing teeth were predominantly located in the mandible and occurred more frequently on the right side. The most common reason for acquired missing teeth was trauma, and no cases of spontaneous loss due to systemic disease were found in this study. Screening for various tooth anomalies is expected to play an important role in cultivating a better understanding of the oral cavity of children, developing healthy dentitions, and contributing to the early detection of some systemic diseases.